EFFECTS OF UNSECURED PERSONAL LOANS ON HOUSEHOLD FINANCIAL HEALTH OF PRIMARY SCHOOL TEACHERS IN EMINING DIVISION, BARINGO COUNTY, KENYA - Kingwara, Robert; Bett, Florence; Bosire, Mary (INTERNATIONAL JOURNAL OF MANAGEMENT & INFORMATION TECHNOLOGY, 2017)
Credit facilities include both secured and unsecured loans. For employees, unsecured personal loans have become more popular due to the relative ease and speed at which they can be obtained. The study focused on three areas namely: evaluate the effects of school fees loans on household financial health of primary school teachers in Emining division, assess the effects of home improvement loans on household financial health of primary school teachers in Emining division, examine the effects of emergency loans on household financial health of primary school teachers in Emining division and establish the effects of development loans on household financial health of primary school teachers in Emining division. The study used descriptive research design. Purposive sampling was used to obtain a sample of 165 respondents, 5 teachers from each of the thirty-three primary schools, in Emining Division, Baringo. A questionnaire was used to collect primary data from the respondent. Correlation analysis was conducted to test the study hypotheses. Results of the study showed that there is a statistical significant positive relationship between unsecured personal loans and household financial health. In particular, there is a statistical positive association between school fees loans, home loans, emergency loans, development loans and household financial of primary school teachers. The study concludes that unsecured loans contributes to the wellbeing of primary teachers.